Capitalist Discourse, Subjectivity and Lacanian Psychoanalysis - Vanheule, Stijn (Frontiers in Psychology, 2016)
This paper studies how subjectivity in capitalist culture can be characterised. Building on Lacan’s later seminars XVI, XVII, XVIII and XIX, the author first outlines Lacan’s general discourse theory, which includes four characteristic discourses: the discourse of the master, the discourse of the university, the discourse of the hysteric and the discourse of the analyst. Next, the author explores the subjectivity and the mode of dealing with jouissance and semblance, which is entailed in a fifth type of discourse, the capitalist discourse, discussed by Lacan in 1972. Indeed, like the other discourses that Lacan discerns, the discourse of the capitalist can be thought of as a mode of dealing with the sexual non-rapport. It is argued that in the case of neurosis the discourse of the capitalist functions as an attempt to ignore the sexual non-rapport and the dimension of the unconscious. Psychosis, by contrast, is marked by an a priori exclusion from discourse. In that case, consumerist ways of relating to the other might offer a semblance, and thus the possibility of inventing a mode of relating to the other. Two clinical vignettes are presented to illustrate this perspective: one concerning the neurotic structure and one concerning the psychotic structure.